Profile and physiotherapeutic intervention of patients victims of trauma admitted to the urgent and emergency unit of a University Hospital in West Paraná (Research, Society and Development, 2022)
Objectives: To characterize the profile of trauma victims admitted to the emergency room of a University Hospital in the West of Paraná and to survey the trauma cases treated by the physiotherapy service, as well as the main approaches and conduct provided. Methodology: Observational, retrospective, cross-sectional and quantitative research, carried out using information from medical records. The sample was collected through a survey of patients who were admitted to the emergency room, totaling 1,020 medical records. Data collection was carried out over a period of one year. The analysis was performed using simple descriptive statistics. Results: The 1,020 medical records were analyzed, of which 17 were excluded because they were not effectively admitted to the emergency room. The total sample of the work consisted of 297 medical records, most of which are male and with a mean age of 40.26 ± 17.48 years. The main cause of hospitalization for multiple trauma was due to traumatic brain injury. 185 patients required invasive mechanical ventilation. As for the final outcome of the patients, only 55 died. 254 patients received physical therapy care. Conclusion: The main cases of multiple trauma patients were male, with a higher prevalence in the diagnosis of Traumatic Brain Injury, either isolated or associated with other traumas. As for the final outcome, most had a satisfactory evolution going from hospital discharge. In relation to physiotherapy, due to the high number of polytraumatized patients requiring mechanical ventilation, there is an emphasis on conducts with an emphasis on respiratory physiotherapy.